The Effects Of Corporate Governance And Accounting Conservatism On Earnings Management - Dudi, Pratomo (2021)
The application of accounting conservatism in Indonesia is reflected in the principles of accounting standards as applied in the preparation of financial statements. By applying conservative accounting policy, managers will be more prudent in recognizing income and expenses to prevent excessive earnings reports. Hence, the application of accounting conservatism can prevent the practice of opportunistic earnings management. The purpose of this study is to determine the corporate governance variables that can encourage the adoption of accounting conservatism and the mediating role of accounting conservatism on earnings management. This study employs the modified Jones (1995) measure of earning's management and Khan and Watts’ (2009) method to measure accounting conservatism. The variables of corporate governance as applied in this research are audit committee independence, audit committee expertise, audit committee meeting, independent director, institutional investors, auditor size, and auditor tenure. This research uses data of financial statements of companies listed on the Indonesian Stock Exchange from 2012 to 2016 by excluding banks and other financial institutions from the sample. A total sample of 67 companies over a period of five years (2012-2016) was used in this study with total data obtained from 335 observations. This study employs a partial least square (PLS) statistical analysis. The results of this study indicate that auditor size encourages the adoption of conservative accounting.